High Frequency Trading and Market Quality - Holmström, Jan (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
There has been remarkable development in technology in the past few years and this change has also shaped the financial markets. Due to the change new players has joined to the markets. These new players are known as a high frequency traders who are able to trade in the matter of milliseconds. Due to these ultra fast traders there has been a lot of controversial information what are they doing to the market quality and also many scholar have been investigating this question while some of them are claiming that the quality of markets have been increasing while others are claiming it has been decreasing due to the high frequency trades. This study will examine high frequency trading’s effects on markets and also scrutinize why the results of earlier studies are so much different. This study will use extended literature review and synthesis as a research method in order to draw a conclusion what is the effect of high frequency traders to market quality and why the results of previous studies are varying so much. The main findings of this study are that markets are more liquid and stable than before due to the high frequency traders. The main reason of the varying results of the earlier studies relies on the data sets what the researchers has been using.

Rahoitusmarkkinoiden luonne on muuttunut huimasti viimeisten muutaman vuoden aikana merkittävän teknologisen kehityksen seurauksena. Teknologisoitumisen seurauksena päivittäinen kaupankäynti on automatisoitunut ja suurin osa kaupasta tehdään algoritmeilla. Valonnopeudella käytävä pörssikauppa tunnetaan nimellä high frequency trading. Tämän valonnopeudella käytävän kaupan seurauksena markkinoilla on ollut paljon ristiriitaista informaatiota siitä mitä se tekee markkinoiden laadulle. Myös monet tutkijat ovat tehneet tutkimuksia aiheesta tuloksien ollessa ristiriitaisia, toisten väittäessä että markkinoiden laatu on parantunut high frequency tradingin seurauksena ja toisten väittäessä markkinoiden laatu on heikentynyt. Tämän tutkielman tavoitteena on selvittää onko high frequency trading ollut haitaksi markkinoiden laadulle ja minkä takia aiempien tutkimuksien tulokset eroavat toisistaan. Tutkimusmenetelminä tämä tutkimus käyttää laajaa kirjallisuuskatsausta ja synteesiä. Merkittävimmät löydökset tämän tutkielman osalta ovat, että high frequency trading on parantanut markkinoiden laatua ja likviditeettiä. Lisäksi merkittävimpänä syynä aiempien tutkimus tulosten eroavaisuuteen on ollut tutkijoiden käyttämät data setit ja high frequency tradingin määritelmä.